(untitled) (Bangladesh Pharmaceutical Journal, 2026)
The present study provides a detailed nutritional profiling of sugarcane juice from eight different varieties grown in Kushtia District, Bangladesh. Among minerals, sodium (Na), potassium (K), calcium (Ca), iron (Fe), and zinc (Zn) were measured by flame photometry and atomic absorption spectroscopy (AAS), while thiamine (vitamin B₁) and riboflavin (vitamin B₂) were estimated by high-performance liquid chromatography (HPLC). In the validation study, all calibration curves exhibited an excellent linear relationship (R² ≥ 0.99). Significant variation among the varieties was detected, and ISD 24 and ISD 18 contained higher amounts of minerals and vitamins. These two varieties of Sugarcane juice are considered as potential dietary sources for electrolytes and water-soluble vitamins and may contribute positively to the development of functional beverage and to public health nutrition in Bangladesh. Bangladesh Pharmaceutical Journal 29(1): 1-7, 2026 (January)